2018
DOI: 10.1097/icl.0000000000000520
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Orthokeratology in Myopia Control: A Review

Abstract: The prevalence of myopia and high myopia has significantly increased worldwide and in the United States. The serious implications of these trends are being recognized. Myopia is not just a minor inconvenience requiring vision correction with glasses or contact lenses, but a disease process creating significant risk of serious vision-threatening eye disease. Various methods of treatment for myopia and myopic progression have been prescribed and studied in effort to find one that is effective, safe, and that pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 78 publications
1
58
0
1
Order By: Relevance
“…Pesudovs et al reported that QIRC score was highest in refractive surgery patients (mean QIRC score of 50.2 ± 6.3), followed by contact lens wearers (mean QIRC score 46.7 ± 5.5), and spectacle wears (mean QIRC score 44.1 ± 5.9) [43]. Orthokeratology (OrthoK) contact lenses (CL) are worn while sleeping to reshape the cornea and are used to correct refractive error and slow the progression of myopia [44]. Quality of life using the National Eye Institute Refractive Error Quality of Life (NEI RQL)-42 questionnaire was evaluated in a group of subjects with low to moderate myopia who had undergone four types of refractive correction, namely, LASIK, OrthoK, soft contact lens (SCL), and spectacles [45].…”
Section: Impact Of Myopia Treatments On Quality Of Lifementioning
confidence: 99%
“…Pesudovs et al reported that QIRC score was highest in refractive surgery patients (mean QIRC score of 50.2 ± 6.3), followed by contact lens wearers (mean QIRC score 46.7 ± 5.5), and spectacle wears (mean QIRC score 44.1 ± 5.9) [43]. Orthokeratology (OrthoK) contact lenses (CL) are worn while sleeping to reshape the cornea and are used to correct refractive error and slow the progression of myopia [44]. Quality of life using the National Eye Institute Refractive Error Quality of Life (NEI RQL)-42 questionnaire was evaluated in a group of subjects with low to moderate myopia who had undergone four types of refractive correction, namely, LASIK, OrthoK, soft contact lens (SCL), and spectacles [45].…”
Section: Impact Of Myopia Treatments On Quality Of Lifementioning
confidence: 99%
“…More recently, it has been proposed that OK has an additional benefit of arresting the progression of myopia (so-called 'myopia control') [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. This is thought to occur as a result of the optical configuration of reverse geometry lenses and its impact on peripheral corneal molding, whereby positive spherical aberration in the molded corneal periphery creates an apparent reduction in the optical stimulus for eye growth [20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the enhancement of unaided vision at daytime, Ortho-K is also able to control myopia progression. Modern Ortho-K lens designs include four zones, namely the central optic zone, the reverse zone, the alignment zone and the peripheral zone [25,26]. The central optic zone helps to flatten the central cornea and is used for refractive correction.…”
Section: Orthokeratologymentioning
confidence: 99%
“…Although Ortho-K is useful for myopic control in numerous studies, all the results were reported as an average value. Lipson et al [26] evaluated the axial length change over 3 years in children receiving Ortho-K treatment. Around 65% of the children had 0.5 mm or less axial elongation, while axial eye growth of more than 1.0 mm was seen in 15% of the children.…”
Section: Orthokeratologymentioning
confidence: 99%
See 1 more Smart Citation